Synthesis and evaluation of value-added products from glycerol / Yusrabbil Amiyati Yusof - Yusrabbil Amiyati, Yusof (2017)
Reactions to produce glyceryl ethers from glycerol were carried out using one-pot and two-step methods. In one-pot synthesis, reaction of glycerol with tert-butanol in the presence of acidic catalyst had resulted in 80 % conversion of glycerol to glyceryl ethers (mono-tert-butoxypropanediol and di-tert-butoxypropanediol) wherein mono-tert-butoxypropanediol is the major component. On the other hand, glyceryl ethers (mono-methoxypropanediol, mono-ethoxypropanediol and mono-tert-butoxy propane- diol) were successfully obtained in the range of 10 % to 45 % yield from the two-step reaction when the ring opening was conducted in basic reaction condition. Meanwhile, glyceryl ethers namely mono-methoxypropanediol, mono-ethoxypropanediol, mono-propoxypropanediol, mono-butoxypropanediol, mono-isopropoxypropanediol, mono-isobutoxypropanediol and mono-tert-butoxypropanediol were successfully synthesized in the range of 15 % to 60 % yield from the ring opening in acidic reaction medium. The in vitro dermal irritection assay showed that glyceryl ethers produced (mono-methoxypropanediol, mono-ethoxypropanediol, mono-propoxypropanediol, mono-butoxypropanediol, mono-isobutoxypropanediol and mono-tert-butoxypropanediol) are classified as non-irritant to the skin as the Human Irritancy Equivalent (HIE) score was below 0.9. In addition, mono-tert-butoxypropanediol was found to be practically non-toxic to aquatic system as the LC50 of the compound was more than 100 mg/L. All synthesized compounds exhibited antibacterial properties against gram positive and gram negative bacteria with 7.5 ± 0.7 mm to 16.0 ± 1.4 mm zone of inhibition. The scaling up process of mono-tert-butoxypropanediol by one-pot reaction (direct etherification method) was conducted for its application evaluations. The etherification was carried out at 1:4 mole ratio of glycerol/tert-butanol in the presence of 5 % acidic catalyst for 5 hours at the temperature of 80 C to 85 C. A product consists of more than 60 % mono-tert-butoxypropanediol with less than 5 % glycerol was successfully obtained in sufficient volume from the scaling up process. The study showed that glyceryl ether (mono-tert-butoxypropanediol) has potential applications in macroemulsion, microemulsion and transparent soap making. Macroemulsions with glyceryl ether showed lower viscosity values (0.48 - 0.51 Pa.s) than macroemulsions with glycerol (0.54 - 0.60 Pa.s). Furthermore, the macroemulsions containing glyceryl ether also exhibited moisturizing property in which the variation in hydration was 27 - 59 % compared to control macroemulsion (variation in hydration = 19 - 34 %). Glyceryl ether is suitable to be used in cosmetic products which require reduced viscosity but retain its skin hydration property. In addition, glyceryl ether is also suitable to be used as a co-surfactant in microemulsion formation. Furthermore, a natural yellow transparent soap with desired transparency value (0.87 ± 0.01) and soap hardness was successfully made by the incorporation of glyceryl ether in the absence of colouring agent. The take-home message from this research is that glyceryl ethers can be synthesized from glycerol via one-pot and two-step reactions, and the findings from the application evaluations of glyceryl ether look promising.